1992
DOI: 10.1111/j.1432-1033.1992.tb17431.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in hepatocyte growth factor mRNA and its receptor in rat liver, kidney and lung

Abstract: Hepatocyte growth factor (HGF) is a mesenchymal‐derived factor which induces mitosis, cell movement and morphogenesis of tissue‐like structure. We analyzed changes in HGF mRNA and its receptor, the c‐met proto‐oncogene product, in the liver, kidney and lung during late fetal and postnatal development in rats. In the liver, the HGF‐mRNA level was very low during late gestation and in neonates, it increased remarkably and reached a maximum two weeks postnatally, to be followed by a decrease to 33% of the maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 50 publications
4
13
0
Order By: Relevance
“…In fetal stages, HGF was not detected in our immunoblotting, which may be consistent with the faint signals in northern blot analysis of previous studies using rats (Calvo et al 1996;Hu et al 1993;Kagoshima et al 1992). Immunohistochemically detectable HGF was also weak.…”
Section: Discussionsupporting
confidence: 89%
“…In fetal stages, HGF was not detected in our immunoblotting, which may be consistent with the faint signals in northern blot analysis of previous studies using rats (Calvo et al 1996;Hu et al 1993;Kagoshima et al 1992). Immunohistochemically detectable HGF was also weak.…”
Section: Discussionsupporting
confidence: 89%
“…In line with previous reports [23,24] , staining for cmet was detected mostly in bronchial epithelium, in cuboidal cells in sacculi, and in cells apparently representing type II cells in alveolar epithelium. Additional staining for c-met was observed in neutrophils.…”
Section: Discussionsupporting
confidence: 77%
“…In the developing rat lung, addition of HGF has been shown to stimulate branching morphogenesis both of alveolar and of bronchial epithelia of the fetal rat lung in organ cultures [11] . A rapid postnatal increase in HGF and c-met mRNA has been reported in neonatal rats, suggesting a role for HGF in lung development also postnatally [24] . Our data of consistent protein expression of HGF and c-met during the perinatal period support a role for HGF in lung development in humans also.…”
Section: Discussionmentioning
confidence: 99%
“…However, as OSM is expressed in the mid-fetal to perinatal liver and its expression level is signi¢cantly decreased after birth, another factor may be involved in hepatic maturation. It was reported that HGF and c-Met are mainly expressed in the ¢rst few days after birth in rat livers [12]. We therefore examined whether expression of HGF in mouse livers is also detected during postnatal stages.…”
Section: Expression Of Hgf and Osm During Liver Developmentmentioning
confidence: 99%
“…These ¢ndings indicate that HGF is an important factor for liver regeneration. It was previously described that mRNAs for HGF and c-Met (the receptor of HGF) were increased at a postnatal stage in several rat tissues such as the liver, lung and kidney [12], suggesting that HGF is involved in the development of these organs.…”
Section: Introductionmentioning
confidence: 99%